Florence Jaffray Hurst Harriman papers - Harriman, Florence Jaffray, 1870-1967.
Correspondence, memoranda, reports, speeches, writings, biographical material, autograph album, newspaper clippings, pamphlets, scrapbook, printed material, memorabilia, photographs, and other papers relating to Harriman's service as a member of the U.S. Commission on Industrial Relations (1913-1916), chairman of the U.S. National Defense Advisory Commission's Committee on Women in Industry (1917-1919), and U.S. minister to Norway (1937-1940). Documents her participation in Woodrow Wilson's 1912 presidential campaign, the American Red Cross Women's Motor Corps in France during World War I, peace organizations including the League of Nations, social reform movements, the Colony Club, New York, N.Y., and the Woman's National Democratic Club, Washington, D.C. Also includes material pertaining to her work on behalf of home rule for the District of Columbia. Autograph album includes a drawing by Louis Raemaekers.
Correspondents include Bernard M. Baruch, Irving Berlin, Albert Einstein, Duke Ellington, Helen Hayes, Cordell Hull, Harold L. Ickes, Estes Kefauver, Archibald MacLeish, George C. Marshall, William Gibbs McAdoo, Claude Pepper, John J. Pershing, Eleanor Roosevelt, Franklin D. Roosevelt, Harry S. Truman, Oswald Garrison Villard, Wendell L. Willkie, Edith Bolling Galt Wilson, and Woodrow Wilson.
Microfilm edition only available of scrapbook, 1912-1913, 1936
Microfilm produced from original in the Manuscript Division.
Diplomat, political activist, and author. Born Florence Jaffray Hurst; died 1967.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Baruch, Bernard M. -- 1870-1965 -- Correspondence; Berlin, Irving, -- 1888-1989 -- Correspondence; Einstein, Albert, -- 1879-1955 -- Correspondence; Ellington, Duke, -- 1899-1974 -- Correspondence; Hayes, Helen, -- 1900-1993 -- Correspondence; Hull, Cordell, -- 1871-1955 -- Correspondence; Ickes, Harold L. -- 1874-1952 -- Correspondence; Kefauver, Estes, -- 1903-1963 -- Correspondence; MacLeish, Archibald, -- 1892-1982 -- Correspondence; Marshall, George C. -- 1880-1959 -- Correspondence; McAdoo, W. G. -- 1863-1941 -- Correspondence; Pepper, Claude, -- 1900-1989 -- Correspondence; Pershing, John J. -- 1860-1948 -- Correspondence; Raemaekers, Louis, -- 1869-1956.; Roosevelt, Eleanor, -- 1884-1962 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Truman, Harry S., -- 1884-1972 -- Correspondence; Villard, Oswald Garrison, -- 1872-1949 -- Correspondence; Willkie, Wendell L. -- 1892-1944 -- Correspondence; Wilson, Edith Bolling Galt, -- 1872-1961 -- Correspondence; Wilson, Woodrow, -- 1856-1924.; Wilson, Woodrow, -- 1856-1924 -- Correspondence; United States. -- Commission on Industrial Relations; United States. -- National Defense Advisory Commission. -- Committee on Women in Industry; American Red Cross. -- Women's Motor Corps; League of Nations; Woman's National Democratic Club (U.S.); Diplomatic and consular service, American -- Norway; Home rule -- Washington (D.C.); Industrial relations -- United States; Peace -- Societies, etc; Presidents -- United States -- Election -- 1912.; Social problems; Women -- Societies and clubs; Women in the labor movement; World War, 1914-1918 -- Manpower; World War, 1914-1918 -- War work -- France; World War, 1914-1918 -- Women; Norway -- Foreign relations -- United States; United States -- Foreign relations -- Norway; Authors; Diplomats; Labor leaders